Treatment of acute cardiac tamponade: A retrospective analysis of classical intermittent versus continuous pericardial drainage. (February 2021) - Stremmel, Christopher; Scherer, Clemens; Lüsebrink, Enzo; Kupka, Danny; Schmid, Teresa; Stocker, Thomas; Kellnar, Antonia; Kleeberger, Jan; Sinner, Moritz F.; Petzold, Tobias; Mehilli, Julinda; Braun, Daniel; et al.
Highlights: Acute cardiac tamponade is a highly relevant complication in modern cardiology. Continuous pericardial drainage is safe and does not increase total drainage volume. Continuous drainage associates with lower rates of open-heart surgical interventions. Continuous drainage associates with reduced re-tamponades and mortality on day 5. Abstract: Background: Acute cardiac tamponade is a life-threatening pathology in modern cardiology as catheter-based interventions become increasingly relevant. Pericardiocentesis is usually the primary treatment of choice. However, protocols for handling of draining pigtail catheters are very variable due to limit data and require further investigation. Methods: We retrospectively analyzed 52 patients with acute cardiac tamponade requiring immediate pericardiocentesis from January 2017 to August 2020. Patients were treated with a classical approach of intermittent manual aspiration or continuous pericardial drainage using a redon drainage system. Results: Mean age of patients was 74 years in both groups. Most common causes for cardiac tamponade were percutaneous coronary interventions in about 50% and transaortic valve implantations in 25% of all cases. 28 patients were treated with classic intermittent drainage from 2017 to 2020. 24 patients were treated with continuous drainage from December 2018–2020. Compared to classical intermittent drainage treatment, continuous drainage was associated with a lower rate of a surgical intervention or cardiac re-tamponade and a lower mortality at 5 days (HR 0.2, 95% CI 0.1–0.9, log-rank p = 0.03). Despite a longer total drainage time under continuous suction, drainage volumes were comparable in both groups. Conclusion: Acute cardiac tamponade can be efficiently treated by pericardiocentesis with subsequent continuous negative pressure drainage via a pigtail catheter. Our retrospective analysis shows a significantly lower mortality, a decreased rate of interventions and lower rates of cardiac re-tamponade without any relevant side effects when compared to classical intermittent manual drainage. These findings require further investigations in larger, randomized trials.